Les univers partagés de science-fiction : pour une transauctorialité - Margot Châtelet (ReS Futurae)
This article proposes the concept of transauthoriality applicable in shared universes of science fiction. To do so, it draws on Saint-Gelais’ concept of transfictionality (2011) and Wolf’s transauthor in Building Imaginary Worlds. This article anchors the concept of transauthoriality in a history of the sociability and collective dynamics of French and American Science Fiction. The aim is to demonstrate that SF authoriality is built on an accumulation of authorial functions (reader, fan, writer, critic, author, cultural passer-by, etc.), and in France it is built on a personal authorial world, in its mediatic extension from the 1970s. SF authoriality is thus above all an authoriality of world. This leads us to a classification of transauthoriality in shared SF worlds, based on Besson (2010), where the world more than the author is at the center of gravitational system, its fictional « veracity » mattering more to the fandom than the authorial figure, which sometimes leads to counter-authorialities or the empowerment of a part of the fandom. The concept of transauthoriality thus allows to reinvest the fan-author of an authorial status, from pseudonymity to authorialization.